Pain catastrophizing and mental health phenotypes in adults with refractory chronic pain: A latent class analysis. (January 2022) - Slawek, Deepika E.; Syed, Madiha; Cunningham, Chinazo O.; Zhang, Chenshu; Ross, Jonathan; Herman, Merrill; Sohler, Nancy; Minami, Haruka; Levin, Frances R.; Arnsten, Julia H.; Starrels, Joanna L.
Abstract: Chronic pain, pain catastrophizing, and mental health disorders such as anxiety or depression frequently occur together and are challenging to treat. To help understand the relationship between these conditions, we sought to identify distinct phenotypes associated with worse pain and function. In a cohort of people with chronic pain on opioids seeking medical cannabis in New York, we conducted latent class analysis to identify clusters of participants based on pain catastrophizing and mental health symptoms of depression, anxiety, post-traumatic stress disorder (PTSD) and attention deficit/hyperactivity disorder (ADHD). We then compared clusters with respect to sociodemographic and clinical characteristics using descriptive statistics. Among 185 participants, we identified four discrete groups: low pain catastrophizing and low mental health symptoms (49% of participants), low pain catastrophizing and ADHD-predominant mental health symptoms (11%), high pain catastrophizing and anxiety-predominant mental health symptoms (11%), and high pain catastrophizing and high mental health symptoms (30%). The group with high pain catastrophizing and high mental health symptoms had the worst pain intensity and interference, disability, insomnia, and quality of life, compared to the two groups with lower pain catastrophizing, though not all differences were statistically significant. Our findings highlight the importance of identifying and addressing pain catastrophizing in patients with comorbid chronic pain and mental health symptoms.